Effect of Drought-Stress Conditions in Chlorophyll Content of Dendrobium sp. Planlets - Fesya Salma Putri; Endang Nurcahyani; Yulianty Yulianty; Bambang Irawan (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Dendrobium sp. was a popular ornamental plant and has high economic value. One of many difficulties in the growth of orchids in Indonesia is low humidity and lack of water availability. Regulatory Substance Growth in the form of an atonic solution can increase the growth of orchid plants. The purpose of this study was to determine the effect of atonic solutions on orchid chlorophyll content in drought stress conditions. This study used a 3x3 factorial design. Factor A is the atonic solution with 3 levels of concentration: 0 mL/L, 2 mL/L, and 3 mL/L. Factor B is PEG 6000 with 3 concentration levels: 0% b/v, 20% b/v and 25% b/v. The parameters tested were chlorophyll a, b and total Dendrobium orchid plantlets. The results showed that atonic solution and PEG 6000 significantly affected the chlorophyll a, b and total content of chlorophyll. The higher concentration of the atonic solution, the more content of chlorophyll a, b and total plantlets of decreased in drought stress conditions in vitro.